2021
DOI: 10.25008/ijadis.v2i2.1219
|View full text |Cite
|
Sign up to set email alerts
|

Use Ordinary Expressions to Learn How to Extract Code Feedback From the Software Program Upkeep Process

Abstract: Software engineering is the manner of making use of engineering studies and alertness packages to the design, improvement and renovation of software program. For software program builders or college students majoring in data engineering, the software program renovation manner is a totally complicated activity. Software renovation manner charges account for 40% to 80% of the whole software program engineering manner. The software program renovation manner is resulting from based programming, inadequate understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…where Psys/A is the power produced per unit area of the blade in W/m 2 [13], [14], Cp is power coefficient, ηtr is transmission efficiency [15], ηb is battery efficiency [16], ηg is generator efficiency [17], ρ is air density in kg/m 3 [18], and v is wind speed in m/s. From the calculations, it is found that the maximum power that can be generated is 7.486 W/m 2 .…”
Section: Methods 21 Calculation Of Generated Power Potentialmentioning
confidence: 99%
“…where Psys/A is the power produced per unit area of the blade in W/m 2 [13], [14], Cp is power coefficient, ηtr is transmission efficiency [15], ηb is battery efficiency [16], ηg is generator efficiency [17], ρ is air density in kg/m 3 [18], and v is wind speed in m/s. From the calculations, it is found that the maximum power that can be generated is 7.486 W/m 2 .…”
Section: Methods 21 Calculation Of Generated Power Potentialmentioning
confidence: 99%
“…As a result, the output of each rule is given explicitly based on the alpha predicate (α), then the final result is obtained using centralized average. [17]. Fuzzy logic is a problem-solving control system methodology that is suitable to be applied to systems, ranging from simple systems to complex or complex systems.…”
Section: B Methodsmentioning
confidence: 99%
“…FIGURE 4 shows a state space block diagram on Simulink for controlling the Eddy current brakes dynamometer system plant using PID control. So it's necessary to make an augmented system equation as in Equation (15). 2) Linear Quadratic Regulator (LQR) Control Proportional Linear Quadratic Regulator (LQR) control is an optimization of a system with state space representation.…”
Section: B Methodsmentioning
confidence: 99%
“…So, this paper discusses the control design simulation on the Eddy current brakes dynamometer system using the LQR control method. The simulation was built using Matlab software [17]. The Eddy current brakes system model used is in the form of state space.…”
Section: Introductionmentioning
confidence: 99%